2015
DOI: 10.5114/pjp.2015.54956
|View full text |Cite
|
Sign up to set email alerts
|

Omentin serum concentration and hepatic expression in chronic hepatitis C patients – together or apart?

Abstract: Chronic hepatitis C (CHC) is accompanied by numerous metabolic disorders, partially associated with altered adipokine system regulation. Omentin (intelectin-1) is a novel adipokine known to play a pivotal role in metabolic regulation in CHC. In a group of 63 CHC patients (29 men/34 women) infected with genotype 1b, aged 6.6 ±14.6 years, serum omentin levels and its gene expression in liver tissue were examined and their association with metabolic and histopathological features was assessed. Serum omentin level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
11
0
4
Order By: Relevance
“…Our previous study of non-obese CHC patients, 16% of whom were cirrhotic, showed significantly higher omentin serum levels compared to healthy controls. However, omentin serum levels were not associated with any histopathological findings[14]. Similar results were found by Nassif et al[18]’ s study, which showed significantly higher serum omentin levels in CHC subjects; however, no information was provided regarding histopathological examination.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…Our previous study of non-obese CHC patients, 16% of whom were cirrhotic, showed significantly higher omentin serum levels compared to healthy controls. However, omentin serum levels were not associated with any histopathological findings[14]. Similar results were found by Nassif et al[18]’ s study, which showed significantly higher serum omentin levels in CHC subjects; however, no information was provided regarding histopathological examination.…”
Section: Discussionsupporting
confidence: 72%
“…The data regarding hepatic omentin expression is equivocal. Our previous study confirmed omentin expression in the liver tissue from chronic hepatitis C (CHC) patients[14]. However, an earlier study by Yang et al[15] found higher omentin expression in the stroma-vascular cells of omental fat and lower expression in the intestine and lung; no expression was observed in the liver, kidney and pancreas.…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations